Kebijakan Manajemen Bencana Di Masa Pandemi Tantangan Ganda Dalam Penanganan Krisis - Navyandhini, Adela Marviola; Saepudin, Eli Apud; Karmila, Diah; Putri, Farah Fadilla; Al Viola Gunawan, Ratu; Zulzana, Tika (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The COVID-19 pandemic has created new complexities in disaster management, presenting multiple challenges for governments and stakeholders in dealing with multiple simultaneous crises. This research examines the adaptation of disaster management policies during the pandemic, focusing on the integration of health protocols in natural and social disaster management. The methodology used includes a comprehensive policy analysis and case studies from various regions that experienced disasters during the pandemic. The results showed that an adaptive approach to disaster management is needed, including modification of evacuation procedures, adjustment of evacuation centers, and strengthening cross-sector coordination. Key challenges identified include limited resources, logistical complexity and the need for specialized protocols to prevent virus transmission in emergency situations. This study recommends developing a more flexible and integrated policy framework, increasing the capacity of the emergency health system, and strengthening multi-stakeholder cooperation in handling multiple crises. The implications of this study contribute to a better understanding of disaster management in the new normal era and the importance of preparedness for multiple hazards.